2009
DOI: 10.1111/j.1096-3642.2008.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

The taxonomy of the endemic golden palm civet of Sri Lanka

Abstract: Two species of palm civet are currently known from Sri Lanka: the widespread common species, Paradoxurus hermaphroditus (Pallas, 1777), and the endemic golden species, Paradoxurus zeylonensis (Pallas, 1778). The latter has two 'morphs', one golden and one dark brown, both of which are recorded from all three major biotic zones in Sri Lanka (wet zone, dry zone, and cloud forest). We have examined specimens of both 'morphs' from all zones, and conclude that there are actually several species involved: names are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 4 publications
3
32
0
Order By: Relevance
“…However, additional molecular evidence is necessary to confirm this. Moreover, the taxonomy within P. zeylonensis has recently been questioned on the basis of morphology (Groves et al. , 2009) and should be investigated in a molecular framework.…”
Section: Discussionmentioning
confidence: 99%
“…However, additional molecular evidence is necessary to confirm this. Moreover, the taxonomy within P. zeylonensis has recently been questioned on the basis of morphology (Groves et al. , 2009) and should be investigated in a molecular framework.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of morphology, Groves et al. () have proposed splitting P. zeylonensis into three or four species, but molecular evidence was lacking in their study. They suggested that golden colour morphs should be attributed to Paradoxurus aureus F. Cuvier, 1822, and brown ones to Paradoxurus montanus Kelaart .…”
Section: Introductionmentioning
confidence: 98%
“…Two recent studies have suggested the existence of cryptic or overlooked species within the Paradoxurus genus (Groves et al. ; Patou et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…From a regional perspective, Sri Lankan primates show the highest diversity per unit land area among south Asian primates (Dittus, 2013). Similarly, the relatively small bodied civets and mongooses (Viverridae) are taxonomically diverse (Groves et al, 2009) and exhibit endemic taxa in all zones with overall 74% endemism. The smaller bodied chevrotains (Tragulidae) among the Artiodactyla have evolved one endemic species widespread from the arid zone (A) to the submontane zone (D2) and another is restricted to the montane zone (D3) (Groves and Meijaard, 2005).…”
Section: The Environmental Arena For Mammalian Diversificationmentioning
confidence: 99%
“…Most recently, morphometric comparisons among loris populations point to two new subspecies (Gamage et al, 2017 online). Phylogenetic studies, in particular, have uncovered at least five new species that formerly were thought of as subspecies (Groves and Meijaard, 2005;Meegaskumbura et al, 2007;Meegaskumbura and Schneider, 2008;Groves et al, 2009;Dissanayake and Oschida, 2012). Baker and Bradley (2006) estimate that genetic investigations will uncover >2,000 new and "cryptic species" worldwide.…”
Section: The Environmental Arena For Mammalian Diversificationmentioning
confidence: 99%